Avaliação da contribuição do contexto social na memória similar à episódica em ratos Wistar - Malheiros, Maria Augustta Sobral de França (2017)
Episodic memory is a type of declarative memory rich in spatial and temporal context. Studies have shown episode-like memory in some animals, criteria that can be shown through behavior, such as events ("what") that occurred in a proper location ("where") and in a certain space of time ("when"). To be considered an episodic-like memory, these behavioral aspects should be evoked in an integrated and associative way, not having the possibility to remember each aspect separately. It is known that the social context influences cognitive and behavioral capacities in different species, but despite its importance, the social context has received little attention from neuroscience and many studies have been directed towards the understanding of the neural processes of behavior, for research with humans or isolated animals. In this study, we sought to evaluate the impact of the social environment on episodic-like memory in Wistar rats. For this, we used 26 male Wistar rats, kept under controlled conditions and divided into three groups: control, experimental unit and experimental dyad. This task is performed in a circular arena and is based on the novelty paradigm. Three sessions were performed in the task: the session of sample 1, sample 2 and test each. The animals of the experimental dyad group were able to integrate the three episodic criteria in the task test session, whereas the animals of the experimental unit and control group did not succeed. The present work is in line with the current trend in the field of neuroscience to conduct experimental designs that will encourage the emergence of behaviors analogous to the natural behavior of exploited species as animal models.